The Correlation Between Self Confidence and Speaking Ability of The Fourth Semester Students of Indo Global Mandiri University - Jesi Utari; Badriyah Ulfah; Desi Surayatika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Speaking is the ability to communicate in everyday life. Being fluent in speaking a specific language becomes a goal in learning the language. In speaking, self-confidence generally appears to be one of the vital variants that may promote either failure or success in language learning. Hence, the purpose of this study was to investigate the correlation between student confidence and speaking ability. This research method was quantitative, and correlation was the design of this study. The research sample was the fourth semester students of Indo Global Mandiri University, which consisted of 37 students. Purposive sampling technique was applied to select the sample and used two types of instruments to collect data from two variables. The data were obtained through giving questionnaires and speaking test to student. In analyzing the data, the researcher correlated the results of the questionnaire and the speaking test results using Pearson Product Moment Correlation. The result of the r count after the data was calculated is 0.694. This value showed that self-confidence and speaking ability have a positive correlation. It was shown by Pearson correlation that the result of the r count is between 0.40 and 0.70. Thus, the students’ self-confidence and speaking ability had significant correlation between the two variables. It suggested that the students needed to maintain their confidence while also improving their speaking ability so that they could speak with fluency and accuracy.